One-pot Synthesis of Imides from Anhydrides in Solid Phase - (Arman) Taherpour, Avat; Abramian, Araz; Kardanyazd, Haniyeh (Asian Journal of Chemistry, 2010)
In this study a simple synthesis of imides by the use of anhydrides and thioacetamide (CH3- CS-NH2) in solid phase is reported.